Jingtian granule alleviates adenine-induced renal fibrosis in mice through SIRT3-Mediated deacetylation of P53 - Xiong, Zhili; Hu, Xinyu; Wang, Rui; Li, Chengyin; Cheng, Huanbo; Zhao, Wei; Shen, Yinfeng; Wang, Linqun; Li, Weinan; Zhu, Xiaoyun; Ba, Yuanming (Frontiers in Pharmacology, 2025)
BackgroundRenal fibrosis is a hallmark and the final outcome of chronic kidney disease (CKD). Jingtian Granule (JT), a traditional formula used in the clinical treatment of CKD for many years. However, the mechanism of action of JT against renal interstitial fibrosis remain unknown.ObjectiveThis study aimed to explore the potential effects and mechanisms of JT on adenine - diet - induced CKD in mice.MethodsRenal interstitial fibrosis was induced in mice by adenine - diet and treated with JT. Renal function was assessed by measuring blood urea nitrogen and serum creatinine levels. Masson’s staining and type I collagen expression were used to evaluate renal collagen deposition. RNA sequencing was used to analyze the expression levels of mRNA in mouse kidney samples after JT treatment. The levels of glutathione (GSH) and malondialdehyde (MDA) were measured to assess lipid peroxidation in the kidneys. Iron metabolism levels were detected by Prussian blue staining and measurement of iron content. The protein levels of SIRT3, P53, glutathione peroxidase 4 (GPX4), and solute carrier family 7 member 11 (SLC7A11) were detected by Western blot. Subsequently, under the premise of SIRT3 knockout, renal function, fibrosis level, iron metabolism level, and lipid peroxidation level were detected, and mitochondrial damage was observed by transmission electron microscope (TEM). In addition, human proximal tubule epithelial cells (HK - 2) were treated with Erastin to induce ferroptosis, followed by exposure to JT. The levels of reactive oxygen species (ROS) were detected.ResultsJT significantly reduced collagen deposition in the kidneys. RNA sequencing identified 20 mRNAs that were differentially expressed in response to JT treatment. Bioinformatics analysis revealed that SIRT3 was a key mRNA regulated by JT. JT activated SIRT3 in fibrotic kidneys to inhibit the acetylation of P53. Under the premise of SIRT3 knockout, JT did not show significant therapeutic effects in inhibiting ferroptosis and fibrosis. In vitro experiments also showed that JT promoted the downregulation of ROS.ConclusionSIRT3 is the key ferroptosis - related mRNA regulated by JT. The ability of JT to modulate the SIRT3/P53 signaling pathway may be a viable approach for the treatment of renal interstitial fibrosis.